(untitled) (International Journal of Engineering and Computer Science, 2017)
In Cloud computing, the information is permanently stored in servers in the internet. From there, the Cloud consumers utilize resources using Virtual Servers and they are charged based on pay-per-use basis. For this, Cloud provider offer two type of provisioning plans, namely On-demand and Reservation plan. They are also called as Short-term and Long-term planning. In general, the reservation plan has minimum cost than on-demand plan. Although the reservation offers the discounted usage price, this option could result in over provisioning and under provisioning problems due to demand uncertainty. There are many kinds of resource provisioning options available in cloud environment to reduce the total paying cost and better utilizing cloud resources. However, the best advance reservation of resources is difficult to be achieved due to uncertainty of consumer’s future demand and providers’ resource prices. In this paper survey the different provisioning options and algorithm. Compare the existing provisioning algorithms with analysis based on cost, availability, uncertainty parameters.